2013
DOI: 10.1101/gad.204453.112
|View full text |Cite
|
Sign up to set email alerts
|

The Prrx1 homeodomain transcription factor plays a central role in pancreatic regeneration and carcinogenesis

Abstract: Pancreatic exocrine cell plasticity can be observed during development, pancreatitis with subsequent regeneration, and also transformation. For example, acinar-ductal metaplasia (ADM) occurs during acute pancreatitis and might be viewed as a prelude to pancreatic intraepithelial neoplasia (PanIN) and pancreatic ductal adenocarcinoma (PDAC) development. To elucidate regulatory processes that overlap ductal development, ADM, and the progression of normal cells to PanIN lesions, we undertook a systematic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(150 citation statements)
references
References 40 publications
7
134
1
2
Order By: Relevance
“…2). Their findings agree with earlier studies reported by Ocaña et al (2012) and of Reichert et al (2013). The plasticity of CSCs and the EMT and MET processes has major implications for the therapeutic targeting of CSCs.…”
Section: Endocrine-related Cancersupporting
confidence: 81%
“…2). Their findings agree with earlier studies reported by Ocaña et al (2012) and of Reichert et al (2013). The plasticity of CSCs and the EMT and MET processes has major implications for the therapeutic targeting of CSCs.…”
Section: Endocrine-related Cancersupporting
confidence: 81%
“…However, these findings do not rule out the possible existence of a subset of ductal cells with a higher degree of plasticity. In fact, recent findings from our labs have provided evidence for a rare subset of Prrx1+ ductal cells with a remarkable degree of sphere forming ability and features of progenitor cells [11] . In fact, Prrx1 ductal cells expanded markedly after cerulein-induced pancreatitis, consistent with a role in pancreatic regeneration after injury [11] .…”
Section: Cellular Plasticity In the Pancreasmentioning
confidence: 99%
“…Cell lines were generated from PanIN-bearing LSL-Kras G12D/+ ;Cre mice (termed KC), 19,24 PDAC-bearing LSL-Kras G12D/+ ;p53 fl/+ ;Cre mice (termed KPfC), 25 and PDAC-bearing LSL-Kras G12D/+ ;p53 fl/+ ;Rosa26 YFP ;Cre (termed KPfCY). 26 In addition, cell lines from PDAC-bearing mice with a global SPARC deletion that have been previously described and characterized 27 were utilized (termed KPfC Sparc -/-).…”
Section: Cell Lines Cell Culture and In Vitro Assaysmentioning
confidence: 99%
“…Strikingly elevated levels of the Etstranscriptional factor Etv1 were observed in these three processes. 19 Approximately 30 Ets factors have been described in mammals, characterized by their conserved helix-turn-helix binding motif, called the Ets domain that binds to the GGAA/T core consensus sequence. 20 Ets factors have been classified into 9 subfamilies, with Etv1 and Etv5 belonging to the PEA3 subfamily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation